Edukasi Anti-Bullying untuk Siswa Sekolah Dasar di Wilayah Pedesaan melalui Pendekatan Sosialisasi dan Role-Playing - Tri Yusnanto; Fatkhurrochman Fatkhurrochman; Sugeng Wahyudiono; Sukris Sutiyatno (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Bullying cases among elementary school students have become increasingly alarming because they negatively impact children’s psychological, social, and moral development, making early intervention essential. This community service project was designed to strengthen students’ understanding and character formation as a preventive effort against bullying behavior. The program was carried out at SD Wonolelo, a rural elementary school, involving 18 sixth-grade students and one accompanying teacher who participated actively in each session. The methods used consisted of interactive socialization and role-playing activities implemented through three stages: delivery of material, interactive question-and-answer discussion, and final evaluation. The results show a significant increase in students’ comprehension of bullying, rising from 30% before the activity to 90% afterward, indicating the program’s strong impact on learning. Beyond improved understanding, the initiative successfully cultivated empathy, cooperation, and social awareness among students so that they not only refrain from bullying but also feel responsible for preventing it within their environment. Overall, the program proved effective in promoting anti-bullying awareness, shaping positive character traits, and supporting the development of a safer and more inclusive culture at the elementary school level.